Regulatory Framework for Social Mapping in Structuring Access to Agrarian Reform - Nur Laili Safitri; Herlindah; Arini Jauharoh (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
the structuring of agrarian reform access and to formulate an ideal regulatory framework to ensure legal certainty. This research employs a normative juridical method using statutory, conceptual, and comparative approaches. The analysis applies grammatical, systematic, and constructive interpretation of primary, secondary, and tertiary legal materials obtained through library research. The novelty of this study lies in its analysis of social mapping as a lex imperfecta under Article 58 paragraph (1) of Presidential Regulation Number 62 of 2023. This study also proposes a legal reconstruction that positions social mapping as a normative prerequisite for ensuring legal certainty in agrarian reform access structuring. The findings reveal that the incomplete regulation of social mapping creates multiple interpretations, weak verification mechanisms, and the absence of sanctions. These conditions result in inaccurate access structuring, low effectiveness in empowering agrarian reform subjects, and an increasing potential for agrarian conflicts. Based on the legal certainty theory of Gustav Radbruch, the regulation has not fulfilled the principle of legal certainty because it is not formulated clearly and operationally. This study recommends legal reconstruction by establishing social mapping as a mandatory procedure supported by standardized operational guidelines, participatory verification mechanisms, Key Performance Indicators (KPI), and clear sanction provisions in order to create a more effective, measurable, and equitable agrarian reform access system.